DOES THE PERCEIVED QUALITY OF APPLICATIONS AFFECT CUSTOMER’S TRUST AND SATISFACTION IN ONLINE FOOD DELIVERY SERVICES - Antonius Adi (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This study aims to investigate and analyze the impact of Perceived Apps Service Quality toward customer trust and customer satisfaction in Online Food Delivery System. This research was conducted using Partial Least Squares - Structural Equation Modeling Method. PLS-SEM 2.0 M3 was used as the software to analyze the data. Results show that Perceived Service Quality affects Customer Trust and Customer Satisfaction. Customer’s trust has a positive effect on Customer Satisfaction in Online Food Delivery Service Context. The limitation of this study are: First, this study only analyzes respondents from Online Food Delivery Service Perspective while there are many other services provided by apps that usually have other services. Secondly, this study only analyzes from the apps quality toward trust while many other factors might contribute toward customer’s trust and the consequences of Trust in Online Food Delivery Service Context. Contribution: This study contributes to the existing Perceived Apps Quality, Customer’s Trust, Customer’s Satisfaction, Relationship Quality, and Online Food Delivery Service Literature. Furthermore, this study can help Marketing Manager of an Online Application based Service company which part of the apps quality that needs to be focused on in building customer’s perceived quality of the apps to gain the trust and satisfaction of their customer. Keywords: Perceived Apps Quality, Customer’s Trust; Customer Satisfaction, Customer’s Behaviour, Online Food Delivery Service